Glass and Plastics Platforms for Foldable Electronics and Displays. (21st July 2015) - Han, Moon Jong; Khang, Dahl‐Young
<x xml:space="preserve">Abstract</x> Reversibly, repeatedly foldable electronics and displays are enabled by employing engineered glass or plastics substrates, where folding deformation is localized in thinned parts only. This design concept can further be extended to dual folding, leading to size reduction down to 1/4. Notably, the foldable electronics and displays can be implemented with no need to introduce any novel materials.